2006
DOI: 10.1038/sj.npp.1301176
|View full text |Cite
|
Sign up to set email alerts
|

D1 and D2 Receptor Antagonist Injections in the Prefrontal Cortex Selectively Impair Spatial Learning in Mice

Abstract: The prefrontal cortex (PFC) is a cortical area involved in selecting and retaining information to produce complex behaviors. Within the PFC, the dopaminergic system plays an important role in information processing. Thus, the objective of this study was to test whether bilateral administration of the D1 and D2 receptor antagonists in the prelimbic region of the PFC influenced the performance of mice in a non-associative spatial learning task. CD1 mice were bilaterally microinjected in the PFC with either the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 67 publications
6
42
0
Order By: Relevance
“…Similar to the present findings, DA receptors blockade within the prefrontal cortex impairs short-term spatial memory, and does not affect novel object discrimination (Rinaldi et al 2007). However, the same pharmacological manipulations within the ventral striatum produce receptors subtype-dependent effect; in particular, D2 dopamine receptor blockade affects both spatial and non-spatial novelty discrimination (Coccurello et al 2000;Rinaldi et al 2007).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar to the present findings, DA receptors blockade within the prefrontal cortex impairs short-term spatial memory, and does not affect novel object discrimination (Rinaldi et al 2007). However, the same pharmacological manipulations within the ventral striatum produce receptors subtype-dependent effect; in particular, D2 dopamine receptor blockade affects both spatial and non-spatial novelty discrimination (Coccurello et al 2000;Rinaldi et al 2007).…”
Section: Discussionsupporting
confidence: 76%
“…Regarding the relative contribution of different DA terminal regions in processing the same kind of spatial information, previous studies reported the effects of D1 and D2 receptor antagonists administration within the prefrontal cortex and the ventral striatum in the same spatial task (Coccurello et al 2000;Rinaldi et al 2007). Similar to the present findings, DA receptors blockade within the prefrontal cortex impairs short-term spatial memory, and does not affect novel object discrimination (Rinaldi et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…Given that this effect was only seen in animals that received extended access to cocaine, it is possible that dysregulation of dopamine D2 receptor signaling contributes to the cognitive deficit, which was also only seen in the LgA group. The integrity of D2 receptor function is closely associated with the ability to manipulate acutely relevant information in prefrontal regions (Wang et al, 2004) and inhibition of D2 receptor activation in both humans and animals, either by antagonist administration or genetic manipulation, results in a decrease in the acquisition of working memory task rules (Glickstein et al, 2005), attentional set-shifting (Tost et al, 2006), and spatial working memory (Von Huben et al, 2006;Rinaldi et al, 2007). This is consistent with the idea that cocaine impaired cognitive flexibility primarily by disrupting prefrontal D2 receptor function.…”
Section: Effects Of Past Experience With Self-administered Cocaine Onsupporting
confidence: 72%
“…The prefrontal dopaminergic function is partly regulated by the enzyme catechol-O-methyltransferase (COMT), which inactivates the synaptic dopamine acting upon D1, the main dopamine receptor at the neocortex [Lidow and Rakic, 1992]. D1 seems to play a crucial role in cognitive processes such as attention [Rinaldi et al, 2007], reward-related incentive learning [Beninger and Miller 1998], executive function, and working memory [Rybakowski et al, 2005]. There appears to be an optimal level for D1 stimulation in regulating prefrontal function and working memory [MeyerLindenberg et al, 2005;Williams and Castner, 2006], which not only relies upon binding efficiency or receptor density [Okubo et al, 1997;Abi-Dargham et al, 2002] but also on its combination with COMT activity and its effects on dopamine levels [Slifstein et al, 2008].…”
Section: Introductionmentioning
confidence: 99%